Cost-effective IE2 high-efficiency single-phase induction motor design and prototyping - Deveci, Ufuk Muhammed; Aycicek, Engin (ELSEVIER - DIVISION REED ELSEVIER INDIA PVT LTD, 2025)
As the utilization of electrical energy has continued to rise, energy efficiency and management has become an increasingly significant issue on the global stage. In this context, the objective of this study was to identify the most efficient and cost-effective production methods by examining the potential for upgrading a single-phase induction motor from the IE1 to the IE2 efficiency class, in accordance with the standards established by IEC 60034-30-1, while minimizing the cost differential. The lamination of the existing motor (IE1) was used in this study, and the impact of the main and auxiliary windings and capacitors on the performance of the motor was analyzed. The reduction of losses was achieved through the optimization of winding, and a finite element method (FEM) was employed in the modeling process. Furthermore, parametric analyses were conducted to identify the optimal capacitors for the selected parameters, resulting in enhanced efficiency. The final results of the parametric analyses were validated by comparing them with the prototype motor produced.
Keywords: Single phase induction motor; IE2 Efficiency; Parametric analysis; Winding optimization; Engineering